Effect of augmented reality-based virtual educational robotics on programming students’ enjoyment of learning, computational thinking skills, and academic achievement - Ou Yang, Fang-Chuan; Lai, Hui-Min; Wang, Yen-Wen (Computers and education, 2023)
The use of educational robotics for programming education has been shown to be effective in fostering students’ computational thinking (CT) skills. However, physical educational robots are expensive, which may limit their wide use in the classroom. This study used augmented reality technology to develop a virtual educational robotic system (AR Bot for short), which offers 3D visual learning feedback to strengthen spatial ability, as well as delayed feedback and auto-scoring feedback to promote students’ deeper CT processes. To examine the impact of AR Bot on programming learning, this study used a quasi-experimental design to compare an experimental group of 41 first-year university students who used AR Bot and a control group of 34 first-year university students who used Scratch. We assessed the impact of the two CT tools on students’ internal learning processes (enjoyment of learning), CT skills (problem decomposition, algorithm design, and algorithm efficiency skills), and academic achievement. The results showed that students who used AR Bot had higher enjoyment of learning, algorithm design skills, and algorithm efficiency skills but not higher problem decomposition skills and academic achievement than students who used Scratch. Enjoyment of learning led to higher problem decomposition, algorithm design, and algorithm efficiency skills but not academic achievement. Problem decomposition and algorithm design skills, but not algorithm efficiency skills, led to academic achievement. The theoretical and practical implications of the proposed tool and other CT tools in programming education are discussed. •AR Bot is a virtual educational robotics with 3D visuals and delayed feedback.•Use of AR Bot promoted students' learning enjoyment compared to Scratch.•AR Bot-induced enjoyment led to higher computational skill dimensions.•AR Bot enhanced students' algorithm design and algorithm efficiency skills.•AR Bot-driven computational skills enhanced students' academic achievement.